2014
DOI: 10.1002/aqc.2534
|View full text |Cite
|
Sign up to set email alerts
|

An index of human alteration of lake shore morphology

Abstract: ABSTRACT1. Morphological degradation constitutes one of the most severe threats to the ecological integrity of lakes. The development of biotic assessment methods for human lake shore alterations using littoral macroinvertebrates requires quantification of the degree of degradation by a stressor index and is complicated through simultaneous physical pressures that alter natural habitat structure.2. The Lake Habitat Survey (LHS) method and macroinvertebrate sampling were used to produce a pan-European dataset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…A key finding of our work is that while, as expected, shoreline morphological alterations decrease physical complexity and diversity of littoral and riparian habitats, the net effect on shoreline complexity was similar for both sites with hard and soft shoreline alterations. Similar results were presented by Miler et al (2015), who showed that habitat diversity of shorelines with high (hard) and medium (soft) morphological alteration was significantly lower, compared with sites with unmodified shoreline features. Concomitantly, shorelines with hard and soft alterations were not significantly different in their habitat complexity scores.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A key finding of our work is that while, as expected, shoreline morphological alterations decrease physical complexity and diversity of littoral and riparian habitats, the net effect on shoreline complexity was similar for both sites with hard and soft shoreline alterations. Similar results were presented by Miler et al (2015), who showed that habitat diversity of shorelines with high (hard) and medium (soft) morphological alteration was significantly lower, compared with sites with unmodified shoreline features. Concomitantly, shorelines with hard and soft alterations were not significantly different in their habitat complexity scores.…”
Section: Discussionsupporting
confidence: 90%
“…Efforts to identify the effects of altered shoreline morphology on littoral invertebrate communities have also increased (e.g., Brauns, Garcia, Walz, et al, 2007; McGoff, Solimini, et al, 2013; Pilotto et al, 2015; Porst et al, 2019; Rosenberger et al, 2008), stimulated by the EC Water Framework Directive (2000/60/EC) requirement to assess the effect of altered hydromorphology on water bodies as a common cause of habitat degradation estimated to account for 10% of European lakes failing to meet their environmental objectives (European Environment Agency, 2018). Hence, there is a growing need for the development of metrics to quantify the morphological degradation at the scale of both the whole lake (Kaufmann & Whittier, 1997; Rowan et al, 2006) and for individual shorelines (Kaufmann et al, 2014; McGoff & Irvine, 2009; Miler et al, 2015; Peterlin & Urbanič, 2013). Existing metrics based on community structure and composition of littoral macroinvertebrates have been tested against morphological degradation metrics to evaluate the potential of these bioindicators for assessing the impact of altered lake morphology (Miler et al, 2013; Urbanič, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Their methodology included a proximity-weighted tally of near-shore human disturbance activities similar to that used in the various USEPA surveys. This lakeshore stress index correlated well with a multimetric index of macroinvertebrate assemblage condition, taxonomic diversity, and the presence of disturbance-sensitive taxa (Miler et al 2015).…”
Section: Discussionmentioning
confidence: 75%
“…Rowan et al (2006) modified the USEPA lake habitat assessment field methodology described by Kaufmann et al (2014b) for application in European Union Water Framework Directive surveys and assessments. Miler et al (2015) developed an index of human alteration of lakeshore morphology using data collected using the methods of Rowan et al (2006) on 51 lakes in seven European countries. Their methodology included a proximity-weighted tally of near-shore human disturbance activities similar to that used in the various USEPA surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Benthic invertebrates are commonly used in bioassessment when considering the wide range of natural habitat preferences, high biodiversity and high sensitivity to diverse environmental factors (Sandin and Johnson, 2000;Jyväsjärvi et al, 2011;Miler et al, 2014). Associations have been demonstrated between benthic invertebrates and variables such as submerged plant abundance (Hanson et al, 2012), substratum (Donohue and Irvine, 2003), total phosphorus, chlorophyll a (O'Toole et al, 2008), dissolved oxygen concentration (Williams, 1996), water level variability (Zohary and Ostrovsky, 2011) and availability of food resources and interspecific interactions among benthic invertebrates, such as competition and predation (Walker, 1998).…”
Section: Introductionmentioning
confidence: 99%